(untitled) (El Hilo de la Fabula, 2024)
In this article we analyze two Argentine translations to Henry James’ ‘novella’. The first translation published in Argentina also happens to be the first translation to Spanish language: it was penned by José Bianco in 1945. This work has an inaugural imprint as the first translation into the language, but it has also been influential on subsequent works in aspects such as the choice of title. On the other hand, Rolando Costa Picazo published in 2005 his own version, titled Una vuelta de tuerca. His retranslation contends against Bianco’s and others for a place within the cultural field and the literary polysystem in Spanish. Between both Argentine translations we can detect several ideas regarding the so called ‘fidelity’ to the original text, strategies to achieve the ambiguity of James’ novella, as well as justifications about the title choice and the type of edition. We argue that two different appreciations of James’ text are at stake between both translations. Bianco’s assumes the challenge of presenting in Spanish language a text known for its ambiguity and aesthetic choices which were held in great regard by literary writers of the period. On the other hand, Costa Picazo’s considers James’ text as a canonical study case which requires critical revision.